Penerapan Total Quality Management pada UMKM untuk Meningkatkan Daya Saing - Dhini Febriani; Nurul Toyyibah; Moh Alvian Syahada; Junaidi Efendi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in Micro, Small, and Medium Enterprises (MSMEs) to improve business competitiveness. In-creasingly intense business competition requires MSMEs to enhance product quality, ser-vice quality, and customer satisfaction in order to survive and grow. The research method used is a quantitative approach with data collection techniques through observation, in-terviews, questionnaires, and literature studies. The research objects were several MSME actors engaged in culinary, trade, and service sectors. The results of the study indicate that the implementation of TQM has a positive effect on improving product quality, opera-tional efficiency, customer satisfaction, and customer loyalty. TQM principles such as cus-tomer focus, continuous improvement, teamwork, and employee involvement have proven effective in increasing MSME competitiveness. In addition, this study also found several obstacles in implementing TQM, including limited capital, lack of understanding of quali-ty management, and limited human resources. Therefore, support from the government and related institutions through training and assistance is needed so that the implementa-tion of TQM in MSMEs can run more optimally. With consistent implementation of TQM, MSMEs are expected to improve business quality and compete more competitively in the modern business era.